Kepastian Hukum dalam Pelaksanaan Asas Kebebasan Berkontrak pada Perjanjian Kredit KPR di Bank BNI Tembilahan - Nia Susanti; Fitri Wahyuni; Wandi (Indragiri Law Review, 2025)
This research originates from the imbalance of positions between banks and customers in Mortgage (KPR) credit agreements. Although the freedom of contract principle is guaranteed under Article 1338 KUH Perdata, in practice, the agreements are unilaterally determined by the bank. This study aims to deeply understand how legal certainty is implemented in the application of the freedom of contract principle in mortgage credit agreements at Bank BNI Tembilahan Branch, as well as to identify the obstacles and efforts made to achieve it. This research employs empirical legal methods with a descriptive approach. Data were collected through in-depth interviews with bank officials, notaries, and customers, as well as document analysis of 30 mortgage credit agreements at Bank BNI Tembilahan Branch for the period 2021-2024. The findings reveal that normatively, the freedom of contract principle has been fulfilled through the existence of a written agreement between the bank and the debtor. However, in practice, this freedom is limited because the agreements use a standard contract format unilaterally prepared by the bank. The main obstacles include customers' lack of understanding of the contract clauses, the dominance of exoneration clauses benefiting the bank, and the potential for default due to unforeseen economic factors. As efforts to ensure legal certainty, Bank BNI Tembilahan Branch conducts socialization of the agreement contents, involves notaries/land deed officials in collateral binding, provides a credit restructuring mechanism for troubled customers, and establishes clear collateral execution procedures in accordance with applicable laws and regulations. This research underscores the need for balance between banking business efficiency and the protection of customer rights as consumers.